Photocatalytic Degradation of Environmental Contaminants: Transformation Products and Effects on Photocatalytic Performance - Moreira, Ailton José [UNESP]; Marques, Gleison Neres; de Araújo, Kelvin Costa; de Moraes, Alex Silva; Mascaro, Lucia Helena; Pereira, Ernesto Chaves (MDPI, 2025)
Advanced oxidation processes are technologies currently being developed and applied to degrade many emerging contaminants that require special attention due to the risks associated with health and the environment. However, the transformation products (TPs) produced by the degradation of these contaminants have attracted little attention from the community regarding their effects on degradation processes, persistence, and environmental toxicity. To present this concern to the scientific community, this article provides data and information that allows us to identify that TPs cannot be pushed to the background or completely ignored in environmental decontamination studies. To this end, heterogeneous photocatalysis was chosen as the primary data collection mechanism due to its interdisciplinary nature. Computational simulation tools, such as Density Functional Theory (DFT), which are widely used to study the properties of materials and contaminants, are very useful and should be applied more frequently to understand the properties of TP. These compounds can interact with photocatalysts and impact the degradation performance of the primary contaminant. Monitoring TPs in degradation reactions is also a challenge due to the lack of analytical standards, the variability of the compounds formed, and the low concentrations produced. The results presented here allow us to conclude that these TPs can affect photocatalytic performance, induce questionable conclusions about their performance, be more toxic than the contaminant of origin, and, above all, contribute relevant information to conclude about the degradation mechanisms.